The sequential treatment of temporomandibular joint ankylosis with secondary deformities by distraction osteogenesis and arthroplasty or TMJ reconstruction. Issue 8 (August 2018) - Zhang, W.; Yang, X.; Zhang, Y.; Zhao, T.; Jia, J.; Chang, S.; Liu, Y.; Yu, Bo; Chen, Y.; Ma, Q.
Abstract: The purpose of this study was to evaluate the sequential treatment of patients with temporomandibular joint (TMJ) ankylosis and secondary deformities by distraction osteogenesis and subsequent arthroplasty or TMJ reconstruction. This study included 40 patients treated at a stomatological hospital in China; they ranged in age from 9 to 53 years (mean age 24.5 years). Ten of these patients were diagnosed with unilateral TMJ ankylosis and 30 with bilateral TMJ ankylosis. Twenty-seven patients also presented obstructive sleep apnoea–hypopnoea syndrome (OSAHS). All patients underwent distraction osteogenesis as the initial surgery, followed by arthroplasty or TMJ reconstruction. Some patients underwent orthognathic surgery to improve occlusion and face shape along with or after arthroplasty or TMJ reconstruction. The therapeutic effects were evaluated in terms of the improvements in maximum inter-incisal opening (MIO), appearance, and respiratory function. After the completion of treatment, all patients showed improvements in MIO and appearance, and the symptom of snoring disappeared. The airway space was significantly increased. Patient follow-up ranged from 6 to 85 months (mean 28.3 months), and four patients experienced relapse. This study suggests that treating TMJ ankylosis with secondary deformities by distraction osteogenesis as the initial surgery and arthroplasty or TMJ reconstruction as the second-stage treatment may achieve favourable outcomes, especially for patients with OSAHS; however, some patients may require orthognathic surgery.